In times of war: typological and morphological characteristics of dwellings in Ḥārat al-Yemen in Izkī, Oman - Bandyopadhyay, Soumyen; Quattrone, Giamila; al-ΚAbrī Haitham N. (Proceedings of the Seminar for Arabian Studies, 2013)
Omani dwelling types remain poorly researched and their potential to reveal important socio-cultural and political shifts largely ignored. Recent fieldwork undertaken at al-Yemen quarter (ḥārah) of Izkī oasis has identified a large number of ’courtyard dwellings’. These stand in contrast to dwellings from important settlements of the Dākhiliyah (Interior) region of Oman, where courtyards are rare. This paper argues that the al-Yemeni dwellings — in spite of their distinctive appearance — are not a distinct type but exhibit instead an ’arrested’ morphological stage within the type already identified in the Interior. Such a development is the product of important tribal, socio-political transformations taking place in Izkī during the eighteenth and nineteenth centuries. A relational ideographic analysis of spatial syntax is undertaken comparing al-Yemen with as-Şaybanī (Birkat al-Mawz) and al-Wista (al-Ḥāmra), supported by extensive ethnographic work at these sites. The long political turmoil that characterized the situation in Izkī, and concomitant economic downturn, resulted in the morphological hiatus. It also reveals the importance of the enclosure in the early control over territory in Oman. The growing prominence of the Darāmikah tribe — especially the Awlād Ghayth clan, and their close alignment with an influential supra-local elite group — will have introduced another typological variant (linear) into al-Yemen. The findings confirm — and also extend — and provide a spatial dimension to John Wilkinson’s seminal social historical findings regarding tribes and agrarian settlements in Oman.